Modern tactics of treatment of constipation - V. V. Skvortsov; E. M. Skvortsova; S. S. Baimankulov (Медицинский совет, 2020)
Constipation (constipation, obstipation) is a symptom in which the frequency of the act of defecation is less than 3 times a week and is accompanied by the release of solid, scanty feces with a feeling of incomplete emptying of the rectum and often requiring additional effort. World health organization in the « International statistical classification of diseases and health-related problems. ICD-10 « refers to constipation diseases (code K59. 0). At the same time, gastroenterological organizations such as the world organization of gastroenterologists and the American gastroenterological Association take a different position, emphasizing that constipation is not a disease, but a symptom. Most often constipation affects young children and the elderly (over 60 years). The feeling of difficulty in emptying the bowel, the impossibility of relief, despite persistent straining, the need to apply additional, stimulating the release of the rectum from the feces, actions (pressure on the perineum, the side walls of the anus, the vagina). The constant state of insufficient emptying of the rectal ampoule often leads to the development of perineal prolapse syndrome. Chronic constipation is diagnosed in cases where the frequency of stool becomes less than 3 times a week, defecation is significantly difficult and requires pronounced efforts, the consistency of the stool is dense, tubercular, there is a feeling of incomplete liberation of the rectum from feces. Constipation is a very common digestive disorder among the population, the tendency to constipation can lead to the development of serious proctological diseases, so this problem has a high degree of social significance. Due to its prevalence and pronounced deterioration in the quality of life of patients, chronic constipation is isolated in an independent syndrome, and currently the problem of constipation is actively studied by proctologists, gastroenterologists and other specialists. This article is devoted to the main issues of modern therapy of constipation.